Different Perspectives on Democracy as an Explanation for the “Populist Radical Right Gender Gap”? - Jansesberger, Viktoria (2024)
The “radical right gender gap” is an established finding in contemporary research, indicating that women support populist radical right parties (PRRPs) in significantly lower numbers than men. Despite substantial literature dedicated to uncovering the reasons behind this gap, significant questions remain unanswered. This article examines the nature of the radical right gender gap in greater detail, focusing on Switzerland—a country with one of the most established PRRPs in Western Europe, the SVP/SPP (Schweizer Volkspartei/Swiss People’s Party), making it a representative case. A defining feature of PRRPs that sets them apart from other parties is their clear distinction between in-groups and out-groups in society, coupled with the propagation of nativist and anti-pluralist values. While PRRPs emphasize caring for the in-group, they often advocate excluding the out-group from rights and privileges. This article argues that the preferences of PRRPs and female voters are in stark contrast regarding these issues. Building on empirical evidence that women place more importance on certain features of a democratic system than men do, we propose that this discrepancy may help explain the gender gap in support for these parties. Utilizing data from the European Social Survey 2020, which includes detailed questions on various understandings of democracy, we find robust support for our hypotheses within the Swiss context. Compared to men, women consider protecting the rights of minorities and safeguarding all citizens from poverty as especially important for a functioning democracy. These preferences emerge as influential factors contributing to women’s reluctance to support PRRPs.